Serum 25‐hydroxyvitamin D as a predictor of mortality and cardiovascular events: A 20‐year study of a community‐based cohort. (9th October 2017) - Zhu, Kun; Knuiman, Matthew; Divitini, Mark; Hung, Joseph; Lim, Ee Mun; Cooke, Brian R.; Walsh, John P.
Summary: Objective: Prospective studies, mostly from Europe and North America, suggest that serum 25‐hydroxyvitamin D (25(OH)D) is inversely associated with mortality and cardiovascular disease (CVD) risk. Data from other regions are limited, and threshold levels for adverse cardiovascular outcomes are uncertain. We examined serum 25(OH)D as a predictor of total mortality and cardiovascular outcomes in an Australian cohort. Design: A 20‐year, community‐based cohort study. Patients: Participants in the 1994/1995 Busselton Health Survey (n = 3946, baseline age 25‐84 years). Measurements: Baseline serum 25(OH)D and mortality and cardiovascular outcomes to 2014 obtained by record linkage. Results: The mean serum 25(OH)D concentration was 60.6 ± 18.0 nmol/L. During 20‐year follow‐up (excluding the first 2 years), 889 participants died (including 363 from CVD) and 944 experienced a CVD event (including 242 with heart failure). In the full cohort, controlling for Framingham risk score variables, higher baseline 25(OH)D was associated with significantly reduced all‐cause mortality (adjusted HR 0.83 per SD increment of 25(OH)D, 95% CI 0.77‐0.90), CVD death (HR 0.85, 95% CI 0.74‐0.96) and heart failure (HR 0.81, 95% CI 0.69‐0.94), but not CVD events (HR 0.99, 0.92‐1.07). In restricted cubic spline regression models, serum 25(OH)D below 65 and 55 nmol/L was associated with higher total mortality and higher CVD mortality/heart failure, respectively. In participants without CVD at baseline (n = 3220), results were similar, but hazard ratios were attenuated and associations with CVD mortality no longer significant. Conclusions: In an Australian community‐based cohort, baseline vitamin D levels below 55‐65 nmol/L are predictive of all‐cause mortality, CVD death and heart failure.